Impact of Group Counseling with Cognitive Restructuring Techniques to Reduce Cheating and Increase Self Efficacy - Kurniasari, Panca; Jafar, Muhammad; Sunawan, Sunawan (Study Program of Guidance and Counseling, Postgraduate Program, Universitas Negeri Semarang, 2021)
Cheating behavior grows from a tolerant attitude towards cheating and low self-efficacy. This research was conducted to test the effectiveness of group counseling with congnitive restructuring techniques to reduce students' attitudes towards cheating and increase the self-efficacy of students at SMA Muhammadiyah 5 Yogyakarta. The experimental method used was randomized pretest-posttest comparison group design, involving 14 students as research subjects who were selected purposively from a total of 123 students in class XI. There are two instruments used, namely Attitude Toward Cheating (ATC) for the attitude scale towards cheating and the Motivated Strategies for Learning Questionnaire (MSLQ) for the self-efficacy scale. The results of this study indicate that cognitive restructuring techniques to reduce attitudes towards cheating and increase student self-efficacy seen from the effectiveness level of cognitive restructuring techniques show that the results are significant. This study confirms the effectiveness of cognitive restructuring techniques to reduce the tendency to cheat by reducing cheating attitudes and increasing self-efficacy.